(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
The experiment was conducted in a village near Lattakia at altitude 10 meter above sea levle during 2017/2018 season. where the onion bulblets (cv.Labani) planted in 15/10/2017.the experiment included four treatments : sheep manure 5kg/m2 , cow manure 15kg/m2, chemical manure 40 g/m2 Urea 46% and the control without fertilizer . The experiment carried out in a simple experiment in the Randomized Complete Block design with three replicates , each replicate included of fifteen plants. The results showed superiority of sheep manure added at rate of 5kg/m2 in some vegetative growth characters : average leaves number per plant 6.767 leaves, average of plant height 60cm , average of leave length 46.4 cm, leaves fresh weigh 47.67 g ,leaves dry weigh 5.74 g, the averagw weigh of the bulb 90 g and the average diameter of bulb 1.807 cm.